Chlorinated polyfluoroalkyl ether sulfonic acids in fish, dust, drinking water and human serum: From external exposure to internal doses. (December 2021) - Wang, Yuan; Li, Xiaotong; Zheng, Zhe; Shi, Yali; Cai, Yaqi
Highlights: 6:2 Cl-PFESA was detected as the third most predominant compound in 100% of the serum samples (n = 439). 6:2 and 8:2 Cl-PFESA are ubiquitous in indoor dust in Shijiazhuang. The estimated daily intakes of 6:2 Cl-PFESA via different exposure pathways were reported for the first time. The observed serum concentrations of 6:2 Cl-PFESA were lower than the modeled data, contrary to its predecessor PFOS. Abstract: Exposure to per- and polyfluoroalkyl substances (PFASs) has raised significant public health concerns due to their persistence and toxicity in the human body. Here, we aimed to investigate the characteristics of exposure to chlorinated polyfluoroalkyl ether sulfonic acids (Cl-PFESAs) and legacy PFASs and the relative contribution from different external pathways to human exposure. Three Cl-PFESAs and fourteen legacy PFASs were detected in human serum, fish, indoor dust and drinking water collected from Shijiazhuang, China. Results showed that 6:2 Cl-PFESA was the third most predominant compound, with an average concentration of 2.70 ng/mL in serum, which was lower than those of perfluorooctane sulfonate (PFOS) and perfluorooctane acid (PFOA) (14.79 and 4.91 ng/mL). The estimated daily intake of 6:2 Cl-PFESA via dust ingestion (mean: 0.008 ng/kg bw/day) was found to be highest among all detected PFASs, while the highest value via fish and drinking water was found for PFOS and PFOA (0.438–9.799 and 0.034–0.155 ng/kg bw/day), respectively. The similar composition of PFASs between serum and fish suggests that fish consumption is a major contributor to human exposure to PFASs. However, the increasing ratios of EDIindoor dust /EDIfish for PFOS, PFOA and 6:2 Cl-PFESA indicated that the contribution of dust ingestion for PFASs, especially 6:2 Cl-PFESA, could not be ignored. The modeled serum concentrations of 6:2 Cl-PFESA higher than its observed levels hint at its gradually increasing exposure levels in the general population. Combined with the lower modeled levels of PFOS than the observed levels, the substituent with 6:2 Cl-PFESA for PFOS is obvious in China. Therefore, further studies on contributions from more detailed external sources and risk assessments of Cl-PFESAs are recommended, especially for some vulnerable subpopulations, considering their widespread exposure and similar environmental behaviors compared with those of their predecessors.